PENGARUH PEMANFAATAN E-JOURNAL TERHADAP KUALITAS PUBLIKASI PENELITIAN MAHASISWA DI UNIVERSITAS UDAYANA - I Dewa Ayu Putu Hartami Indraswari; I Ketut Gede Harsana; Ni Putu Premierita Haryanti (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2025)
This final project is entitled "The Effect of E-Journal Utilization on the Quality of Student Research Publications at Udayana University". The formulation of the problem in this study is how the effect of e- journal utilization on the quality of student research publications at Udayana University. This study aims to determine the effect of e-journals on the quality of student research publications at Udayana University. The sample is Udayana University students who have written journals and articles and Udayana University students who are at least in semester 7, totaling 98 people. The data collection technique uses a questionnaire consisting of two independent variables, namely E-Journal Utilization and Student Research Publications. The results of the study indicate that the influence of E-Journal Utilization on the Quality of Student Research Publications at Udayana University is included in the very influential category, where the Accuracy variable (Y2) has the highest value of 82.34%, while the lowest value is the Overall variable (Y1) at 79.1%. The results of the validity test indicate that all statements submitted are valid, and the reliability test on the two existing variables shows reliable results.